Effectiveness of clopidogrel vs. ticagrelor based on the ABCD-GENE score in acute coronary syndrome patients following percutaneous coronary intervention - Xu, Xiaotong; Na, Kun; Qiu, Miaohan; Yang, Xueqing; Qi, Zizhao; Li, Jing; Xu, Kai; Wang, Xiaozeng; Li, Yi; Han, Yaling (Frontiers in Pharmacology, 2025)
AimThis study employs the ABCD-GENE score (age, body mass index, chronic kidney disease, diabetes, and CYP2C19 variants) to compare the effectiveness and safety of clopidogrel versus ticagrelor-based DAPT in ACS patients post-PCI.MethodsA total of consecutive 21,705 ACS patients who underwent PCI between March 2016 and March 2023 and survived at discharge were included. The primary outcome was a composite of ischemic and bleeding events within 12 months, including cardiac death, myocardial infarction, ischemic stroke, and BARC types 3 or 5 bleeding. Propensity score matching was performed to balance baseline characteristics between clopidogrel and ticagrelor-based DAPT.ResultsIn the ABCD-GENE score <10 group, (4,748 matched pairs), ticagrelor increased BARC 3 or 5 bleeding (1.9% vs. 1.1%; HR: 1.52; 95% CI, 1.18–1.96; P = 0.0018), with no difference in the primary outcome (3.0% vs 3.5%; HR: 1.17; 95% CI: 0.94–1.46; P = 0.17) or ischemic events (2.0% vs 1.6%; HR: 0.82; 95% CI: 0.60–1.10; P = 0.19), compared with clopidogrel. In the ABCD-GENE score ≥10 group (1,231 matched pairs), ticagrelor significantly reduced the primary outcome (4.1% vs 6.0%; HR: 0.67; 95% CI: 0.47–0.96; P = 0.0272), driven by reduced rates of ischemic events (2.2% vs 4.5%; HR: 0.57; 95% CI: 0.38–0.85; P = 0.0015), without an increase in BARC 3 or 5 bleeding (1.9% vs. 1.7%; HR: 1.08; 95% CI, 0.60–1.96; P = 0.79), compared with clopidogrel.ConclusionThe ABCD-GENE score showed good predictive accuracy for a composite of ischemic and bleeding events and could identify patients likely to benefit from the ticagrelor-based antiplatelet strategy.